An Introduction to Indonesian Wild Shiitake - Ivan Permana Putra; Mada Triandala Sibero; Saipul Sihotang; Lilis Supratman; Rudy Hermawan; Oktan Dwi Nurhayat (HAYATI Journal of Biosciences, 2023)
Pegler suggested that shiitake comprises three morphological species: Lentinula edodes (continental and northeast Asia), L. lateritia (tropical Asia and Australasia), and L. novae-zelandiae (New Zealand). The current study reported for the first time the occurrence of L. lateritia (Berk.) Pegler in Indonesia. During a fungus foray in Kerinci (Jambi, Sumatra, Indonesia) in 2022 and 2023 by the Indonesian mushroom hunter community, some basidiomata of Lentinula were obtained. At a glance, our specimens resembled L. edodes. The current study aims to justify the taxonomical position of our specimens based on morphological and molecular data. The fresh basidiomata were used for morphological and molecular analyses. The molecular work was done using ITS 4/5 Primers for phylogenetic analysis of rDNA-ITS region. Morphologically, the uniformly reddish brown, smooth, and glabrous of pileus confirmed our specimens as L. lateritia. In addition, the absence of a range of colors and squamules pileus distinguished L. lateritia BO24628 form L. edodes, while the formation of florets cheilocystidia in L. madagasikarensis was the distinctive character of our specimens. The BLAST result revealed that our specimen has high similarity (99-100%) with L. lateritia and L. edodes as the top hits. The phylogenetic tree (RAxML) nested our specimens in the L. lateria clade and is closely related to one specimen from Papua New Guenia (PNG) (BS 98%). In addition, L. lateritia BO24628 has a sister clade of the specimen from PNG and Australia. Moreover, we provide the herbarium collection of wild L. lateritia in Indonesia.